Aplicação da baropodometria no desenvolvimento de um protocolo de avaliação motora em crianças nascidas pré-termo após a aquisição da marcha - Coldebella, Cristiane (2016)
Preterm birth contributes significantly to the increase of morbidities associated with motor development, making essential the continuous monitoring of these children. Thus, baropodometry analysis by consisting of a quantitative method for postural control can be advantageous for the diagnosis and monitoring of engine development of children. This study aimed to develop a motor evaluation protocol through the data and baropodometric indexes in preterm infants. It was a descriptive study, which were evaluated 103 children between 24 and 59 months. Of these, 40 preterm and 63 term infants. During the sample selection was completed an evaluation form with data from medical records corresponding to the pre-term group and a questionnaire to parents on group term. After, body mass and height were measured, then the implementation of the Motor Development Scale. Finally, baropodometry was held in static form, with three replicates, which consisted of 5 seconds of child adjustment bend the plate and 30 seconds which were measured static analysis data: plantar pressure and pressure swing center area. After, the plantar pressures were transformed into indexes, the anteroposterior index was defined by the anterior and posterior plantar pressures: API = 1-2 * │0,6-P│; and side side index, in turn, defined by the right and left side planter pressure: SSI = 1- │RS-LS│. After evaluating, the data were submitted to normality test of Shapiro-Wilk distributions, being checked the non-normal distribution, the Mann-Whitney test was used to verify differences between groups, the association between the values obtained by baropodometry analysis, Motor Development Scale, and the main characteristics and complications of preterm group was verified by Spearman correlation. Significant difference in the values of SSI (p = 0.000) among term infants and infants born preterm were observed, and this difference has moderate correlation with gestational age (ρ = 0.304) compared to the pressure oscillation center , full-term babies showed less fluctuation compared to chronological age (ρ = -0.354), and this relationship was contrary in preterm children (ρ = 0.336).When only analyzed the preterm group, it was found that the SSI had moderate and inverse correlation with the length of stay (ρ = -0.353) and the duration of mechanical ventilation (ρ = -0.317) and the air oscillation center pressure showed moderate and direct correlation with noninvasive ventilation time (ρ = 0.341).The mass at birth showed moderate correlation with SSI (ρ = 0.359) and also with the motor age (ρ = 0.323) and the ratio engine (ρ = 0.341) and strong correlation with gestational age (ρ = 0.898) in contrast current weight showed moderate correlation with the motor quotient (ρ = 0.310) and gestational age(ρ = 0.381) and strong correlation with the motor age (ρ = 0.555) and chronological age (ρ = 0.613). There was significant difference in the age of acquisition of march of the children who needed physical therapy monitoring of those who did not needed (p = 0.013). A smaller SSI index in premature infants, may be related to hospitalization time and mechanical ventilation, in addition to mass at birth, already the largest air pressure oscillation center has correlation with noninvasive ventilation time.It may also be seen that the current mass and chronological age influenced more motor development than the mass at birth and gestational age in preterm children.